Benchmarking in Tourism Destination, Keeping in Mind the Sustainable Paradigm - Valentina Bosetti; Mariaester Cassinelli; Alessandro Lanza (Fondazione Eni Enrico Mattei (FEEM), 2006)
Tourism destination benchmarking and the assessment of tourism management performances are a crucial and challenging task in the direction of evaluating tourism sustainability and reshaping tourism activities. However, assessing tourism management efficiency per se may not provide enough information concerning long-term performances, which is what sustainability is about. Natural resources management should therefore be included in the analysis to provide a more exhaustive picture of long-run sustainable efficiency and tourism performances. Indeed, while the environmental endowment of a site is a key feature in tourism destination comparison, what really matters is its effective management. Therefore, in this paper we assess and compare tourism destinations, not only in terms of tourism services supply, but also in terms of the performance of environmental management. The proposed efficiency assessment procedure is based on Data Envelopment Analysis (DEA). DEA is a methodology for evaluating the relative efficiency when facing multiple input and output. Although the methodology is extremely versatile, for the sake of exemplification, in this paper it is applied to the valuation of sustainable tourism management of the twenty Italian regions.
Keywords: L83; Q26; 330; Data envelopment analysis; Sustainable tourism indicators; Tourismus; Data-Envelopment-Analyse; Nachhaltige Entwicklung; Italien